2010
DOI: 10.1007/s00280-010-1244-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage induced by the anthracycline cosmomycin D in DNA repair-deficient cells

Abstract: Cosmomycin D induced time-dependent apoptosis in nucleotide excision repair-deficient fibroblasts. Despite similar apoptosis levels, cosmomycin D caused considerably lower levels of DNA damage compared to doxorubicin. This may be related to differences in structure between cosmomycin D and doxorubicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…Furthermore, doxorubicin caused greater DNA damage in normal than in tumor cells when compared to coronaridine. Carvalho et al (2010) compared the effect of the anthracycline cosmomycin D and doxorubicin in DNA repair-deficient cell lines (XP-A and XP-C). Treatment of XP-A and XP-C cells with cosmomycin D induced apoptosis in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, doxorubicin caused greater DNA damage in normal than in tumor cells when compared to coronaridine. Carvalho et al (2010) compared the effect of the anthracycline cosmomycin D and doxorubicin in DNA repair-deficient cell lines (XP-A and XP-C). Treatment of XP-A and XP-C cells with cosmomycin D induced apoptosis in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Development of resistance to chemotherapeutic drugs poses a serious limitation to the effectiveness of treatment [10,11]. For example, it has been shown that acquired resistance to Pt accounted for treatment failure and deaths in up to 90% of patients with ovarian cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high intracellular GSH concentration can result in the formation of aggregates of the DOX loaded micelle cores, which remain in the cells favourably and reduce the efflux of drug out of cells further . Hence more DOX can get into the nuclei of cancer cells to stop DNA replication, inhibit macromolecular synthesis, and ultimately kill the cancer cells …”
Section: Resultsmentioning
confidence: 99%